Multiple amplification detection of microRNA based on the host–guest interaction between β-cyclodextrin polymer and pyrene1. Issue 12 (21st June 2015) - Guo, Xiaochen; Yang, Xiaohai; Liu, Pei; Wang, Kemin; Wang, Qing; Guo, Qiuping; Huang, Jin; Li, Wenshan; Xu, Fengzhou; Song, Chunxia
<x xml:space="preserve">Abstract</x> The proposed multiple amplification strategy based on the host–guest interaction between β-CDP and pyrene is homogeneous, sensitive and rapid.